The Quality Of Public Services In The Context Of Managing Temporary Residence Certificates (SKTS) In Landungsari Village, Dau District, Malang Regency - Didik Supriyanto (Jurnal Indonesia Sosial Teknologi, 2023)
Landungsari Hamlet is one of the villages in Dau District, Sial Regency which provides public services at the Village Office. Public services for population administration in Landungsari Village, Dau District include making Family Cards (KK), Electronic Citizen Characteristics Cards (e-KTP), Reverse Residence Records (SKTS) and there are recommended services including: making birth certificates, marriage certificates, certificates land, business license (HO), introduction to making SKCK and SIM. Based on the results of studies that have been tested regarding the quality of public services from the perspective of population administration in Landungsari Hamlet, it can be concluded that Landungsari Village has a room size of 8x6m2 for a capacity of 5 service personnel. The service room has service tables, an activity table, 2 sets of residence description card recording devices and remote chairs for people waiting for service. The Landungsari Hamlet office has not yet fulfilled the necessary service tools to provide services to similar communities while at least there are chairs in the waiting room, there is no table for writing in the waiting room, information equipment is not yet available. Tools such as generators are not optimized, so when the power goes out, the service method will also end the totality, which means that people cannot get service. In terms of reliability, from the results of a leaked study if the residents of Dau District are satisfied with the services provided by the Ordinary Services Section of Dusun Landungsari in terms of reliability